A linguagem audiovisual no processo educativo e no incentivo à leitura : o caso do programa Mundo da Leitura - Serafini, Denise Jorge (2009)
This study consists in analyzing the way how the audiovisual feature is used in the educational process and the mediations established in its reception in the classroom. For that, it was developed a case study through field observation, in-depth interview and questionnaire with students. The research addresses the practice of using the audiovisual program in the Mundo da Leitura to encourage reading in a class of third grade, of a school in the municipal system of education of Passo Fundo. The text articulates concepts on reading comprehension, audiovisual language as a stimulus for learning and for the teacher's relationship with the media. It also proposes, based on an approach between the Cultural Studies and the Studies of Reception, in a view of the multi mediations of Guilherme Orozco, the analysis of the sources of mediations activated by the use of the program on the school context. We understand that the individual lives in cultural contexts filled with the means of mass communication and that the audiovisual features have pedagogical possibilities which can be optimized by the approach between the areas of knowledge of communication and education. Starting from the readings made and in front of the facing with the results, we point at the potentiality of the audiovisual feature in a sense of stimulating the reading and contributing to the learning, reinforcing the mediations set in the context of the reception in the classroom. However, it must be considered that for a good job it is important to maintain the focus of the audiovisual feature as an attractive and different tool to stimulate learning, besides requiring from the teacher knowledge around the language and around the matter shown towards this proposal